By the Honorable Thomas Fitch Esq ; governor, and commander in chief of His Majesty's English colony of Connecticut ... A proclamation : ... that a publick thanksgiving, be observed ... on the twenty-sixth day of November, next ... Given under my hand at the Council-chamber, in New-Haven, the twenty-seventh day of October ... 1761 ([Printed by James Parker, and Co.], 1761)
October 27, 1761 broadside issued by Governor Thomas Fitch of Connecticut, proclaiming November 26th as a day of public thanksgiving in light of the crowning of the new king, George III and the royal family.